Autonomic Function Impairment and Brain Perfusion Deficit in Parkinson’s Disease - Lin, Wei-Che; Chen, Pei-Chin; Huang, Chih-Cheng; Tsai, Nai-Wen; Chen, Hsiu-Ling; Wang, Hung-Chen; Chou, Kun-Hsien; Chen, Meng-Hsiang; Chen, Yi-Wen; Lu, Cheng-Hsien (Frontiers in Neurology, 2017)
Introduction Autonomic disorders have been recognized as important Parkinson's disease (PD) components. Some vulnerable structures are related to the central autonomic network and have also been linked to autonomic function alterations. The aims of the study is to evaluate the severity of the autonomic dysfunction and the cortical hypoperfusion using arterial spin labeling (ASL) MRI. And then, possible relationships of significant between-group differences in perfusion pattern to clinical variables and autonomic functions were examined to determined the pharmaceutical effects of dopaminergic treatment on cerebral blood flow (CBF) in patients with PD. Methods Brain ASL MRI was carried out in 20 patients with PD (6 men and 14 women, mean age: 63.3 ± 6.4 years) and 22 sex- and age-matched healthy volunteers to assess whole-brain CBF and the effects of dopaminergic therapy on perfusion. All subjects underwent a standardized evaluation of cardiovagal and adrenergic function including a deep breathing, Valsalva maneuver (VM), and 5-minute head-up tilt (HUT) test. Perfusion MRI data were acquired on a 3.0T scanner with a pulsed continuous ASL technique. The CBF, autonomic parameters, and clinical data were analyzed after adjusting for age and sex. Results Patients exhibited a decline in autonomic function (rapid heart rate in response to deep breathing, low baroreflex sensitivity, high systolic and diastolic pressure, and altered tilting test response), widespread low CBF, and robust response to dopaminergic therapy. Lower perfusion in the middle frontal gyrus was associated with increased clinical disease severity (UPDRS I score, p<0.001). Lower perfusion in autonomic control areas, such as the frontal lobe and insula, were significantly associated with autonomic impairment (p<0.001). Conclusions Our study indicates that PD is a progressive neurodegenerative disorder that changes the perfusion of central nervous system and is associated with variable autonomic dysfunctions. Neuronal loss and sympathetic activation may explain the interaction between cortical autonomic region perfusion and cardiovascular autonomic function.